PENGARUH CORPORATE GOVERNANCE DAN INTANGIBLE ASSETS TERHADAP FINANCIAL DISTRESS - Hasniati Hasniati; Biana Adha Inapty; Eni Indriani (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2017)
The objective of this study is toexamine the influence of corporate governance and intangible assets to ward financial distress. Corporate governance in this study is measured by board of directors, independent board, institutional ownership, managerial ownership and the audit committee. Intangible assets used in this study are measured by allintangible assets owned by the company. The populationin this study is all manufacturing companies listed on the Indonesia Stock Exchange, which continuously published financial statements in 2010-2012. Based on purposive sampling method, the sample consisted of 21companies in the period 2010-2012 in order to obtain 63 observation data. Financial distress in this studyis measured by the AltmanZ-score. Hypothesis testing based on multiple linearr egressions showed that the board of directors and independent board have positive influence on financial distress. The result also showed that managerial ownership has negative influence on financial distress, while institutional ownership, audit committee and intangible assets has no influence on the financial distress.